(3cJGH aj HjGf eWGdH YLjHIs
(3ChdgG (B:s
(3gPg eSCdI aj bhe jMJLhf HGdbOQ hjbhdhf bO bVj GdCeQ hjMJLhf Hbhdg JYGdi(B: "(3Ef Gddg SHbJ dge efG GdoMSfi ChdFc YfgG oeHOYhf(B" s
(3BNQgG (B:s
(3Je GdLhGH HYhf Gdedc GdhgGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B19s
(3GdfSNI HgG MhGTs
(3hQOJ CjVkG JMJ Qbe (B18/430s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdEeHQhRjGfG (B(D 404) s
Keywords: (3GdJhMjO hGdedd hGdfMds